Development and Standardization of a Scale to Measure Farmers’ Risk Perception towards Climate Change - Gupta, Brijesh Kumar; Pathak, Deepak Kumar; Mishra, Gaurav; Suryavanshi, Ashutosh; Mishra, Bhanu Prakash; Singh, Lakhwinder (Indian Journal of Extension Education, 2026)
Farmers’ perceptions of risks related to climate change significantly influence their adaptation behaviour and their responses to climatic stressors. The present study sought to develop and standardize a valid and reliable scale to quantify farmers’ risk perception of climate change. Using the Likert summated rating technique, an initial pool of 70 statements was generated based on a review of the literature and consultation with experts. After systematic editing and relevancy testing through expert judgment, 45 statements were screened, and 28 statements were subjected to item analysis using responses from 40 farmers in a non-sampled area. Based on discriminating power (‘t’ value ≥ 1.75) and reliability criteria, 22 statements were finally selected for inclusion in the scale. The reliability of the scale was established using Cronbach’s alpha, which exceeded the acceptable threshold of 0.70, representing high internal consistency. Content validity was ensured through comprehensive coverage of climate-related risks affecting crop, livestock and livelihood systems. The final scale enables categorization of farmers into low, medium, and high levels of climate change risk perception. The developed scale is a useful tool for researchers, extension professionals, and policymakers to assess farmers’ risk perception and to design location-specific, evidence-based climate change adaptation and extension interventions.